Peran Perhatian Orang Tua Terhadap Akhlakul Karimah Siswa di Madrasah Ibtidaiyah - Adawiyah, Robbi Atul; Sahri, Iksan Kamil (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This research aims to find out the role of parental attention on students' morals at MI AR-Rahman Parengan Jetis Mojokerto. This research uses a qualitative approach. Data collection techniques used in this research include observation, interviews and documentation. This research uses qualitative data analysis which consists of three stages, namely data reduction, data display, and conclusion or verification. The results of this research found a diversity of morals in students which was influenced by the role of parental attention in developing their children's morals. Based on research results, the majority of children who have madzmumah morals are influenced by the lack of attention from their parents, they tend to carry out despicable morals due to the lack of parental direction in developing children's morals in everyday life, so when they do despicable morals they think This is a natural thing and to get attention from the surrounding environment. This is very different from children who receive the role of attention from their parents. They tend to have morals because they receive the role of parental attention and direction in having morals in everyday life.